2014
DOI: 10.3390/foods3010110
|View full text |Cite
|
Sign up to set email alerts
|

Eggs and Poultry Purchase, Storage, and Preparation Practices of Consumers in Selected Asian Countries

Abstract: The objective of this study was to begin characterizing purchase, storage, handling, and preparation of poultry products and eggs by selected consumers in three Asian countries: India, Korea, and Thailand. Approximately 100 consumers in each location were recruited to participate in this study. The consumers were surveyed about eggs and poultry purchase behavior characteristics, such as temperatures and locations, storage behavior, such as storage locations in the refrigerator or freezer, preparation behavior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
(37 reference statements)
3
27
1
Order By: Relevance
“…In this study, we further explored whether dietary LP or TP could affect lipid peroxidation of eggs under longterm storage conditions. However, it should be noted that our study is not intended to propagate the storage of raw eggs at room temperature, although consumers in Asian (Koppel et al, 2014) or European (Koppel et al, 2015) countries might buy eggs stored at room temperature from various sources such as farmers, local markets, or stores. It has been reported that egg quality influences consumer acceptance and this decreases as the storage time at room temperature increases (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we further explored whether dietary LP or TP could affect lipid peroxidation of eggs under longterm storage conditions. However, it should be noted that our study is not intended to propagate the storage of raw eggs at room temperature, although consumers in Asian (Koppel et al, 2014) or European (Koppel et al, 2015) countries might buy eggs stored at room temperature from various sources such as farmers, local markets, or stores. It has been reported that egg quality influences consumer acceptance and this decreases as the storage time at room temperature increases (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Eggs usually were refrigerated in the USA at the time of purchase, and similar practices have been observed in Estonia (18) and Korea (17). Eggs during purchase were at room temperature in Colombia and Argentina, as well as in India (17), Italy and Spain (18).…”
Section: Discussion Purchase and Storage Behaviormentioning
confidence: 80%
“…Purchasing fresh eggs from a farmer's market has not been found common in selected Asian countries (17) or in selected European countries, either (18). Total of 17 and 20% of consumers purchased eggs from the farmer directly or raised their own chickens in Colombia and Argentina, respectively.…”
Section: Discussion Purchase and Storage Behaviormentioning
confidence: 99%
See 2 more Smart Citations